Mediatisation and regional campaigning in a party-centred system - Skogerbo, Eli (Javnost (Ljubljana), 2014)
Election campaigns are central to political life as well as to the study of political communication and provides much empirical knowledge about the processes of mediatisation and mediation of politics. Most often studies focus on the campaigns featuring the national top politicians. However, most elections campaigns in Western democracies are run by party branches and candidates who rarely make the top headlines in the nationwide media, yet they are also dependent on media attention and agenda-setting to be visible and reach their voters. Relying on several data sets from studies of the Norwegian 2009 parliamentary election campaign, this study asks, first, how regional, mainly "non-celebrity politicians", obtain visibility. We seek to unravel how the media logic works on the regional and local level. Second, we ask why it is important for candidates in a party-centred proportional (PR) system to be visible. Our findings suggest that we should recognise the mediatised and multileveled character of election campaigns in order to understand how media logics work below the nationwide setting.
Keywords: election; volitve; politična kampanja; communication; komuniciranje; odnosi z javnostmi; politične komunikacije; politična propaganda; mass media; množični mediji